1986
DOI: 10.1111/j.1365-2362.1986.tb01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma 3,4‐dihydroxyphenylethylene glycol (DHPG) and norepinephrine levels as indices of sympathetic activity in man

Abstract: Plasma levels of norepinephrine (NE) and the NE metabolite 3,4-dihydroxyphenylethylene glycol (DHPG) were measured simultaneously following sympathetic activation induced by standing, cold pressor testing and bicycle exercise at progressively increasing workloads in normal volunteers. Free DHPG and NE levels both increased with sympathetic activation, but free NE levels were a more sensitive index of change. In addition, plasma free NE levels more closely reflected the fall in heart rate following exercise tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…When plasma NE was markedly sup- ministration ofthe alpha-2 adrenoceptor antagonist YOH and similar absolute decreases, after oral administration of the alpha-2 adrenoceptor agonist clonidine. The present findings are in agreement with those of others involving measurements of plasma DHPG in humans or laboratory animals (3,(11)(12)(13)(14)(15)(16)(17)(18)(19). Whereas similar changes in NE and DHPG during altered release of endogenous NE have led others to conclude that simultaneous measurement of plasma DHPG and NE does not offer important advantages over NE alone in the assessment of sympathetic function (19), the results reported here about effects of neuronal uptake blockade lead to a different conclusion.…”
Section: Clonidinesupporting
confidence: 82%
See 1 more Smart Citation
“…When plasma NE was markedly sup- ministration ofthe alpha-2 adrenoceptor antagonist YOH and similar absolute decreases, after oral administration of the alpha-2 adrenoceptor agonist clonidine. The present findings are in agreement with those of others involving measurements of plasma DHPG in humans or laboratory animals (3,(11)(12)(13)(14)(15)(16)(17)(18)(19). Whereas similar changes in NE and DHPG during altered release of endogenous NE have led others to conclude that simultaneous measurement of plasma DHPG and NE does not offer important advantages over NE alone in the assessment of sympathetic function (19), the results reported here about effects of neuronal uptake blockade lead to a different conclusion.…”
Section: Clonidinesupporting
confidence: 82%
“…In subjects treated with DMI at a dose previously shown to inhibit uptake-l effectively (9, 10), plasma DHPG decreased to a similar concentration range. These results, consistent with those of others about effects of clonidine or uptake-l blockade on plasma DHPG (12,(14)(15)(16)(17)(18)(19)(20) suggest that basal release of DHPG depends on a source other than NE recaptured by uptake-l. According to the model in Fig.…”
Section: Clonidinesupporting
confidence: 82%
“…The ratio of NE to DHPG (the major CNS metabolite of NE) [14] has been utilized as an index of active noradrenergic function by comparing the relative activity of NE release to uptake [18,19]. Elevated ratios have been observed in plasma during physical exertion [19][20][21], and in the CSF following sympathetic disinhibition [16], and decreased ratios have been noted in animals exposed to sympatholytics [22]. Elevations in CSF levels of catecholamine compounds and metabolites have previously been described for various neurological and psychological conditions in which increased sympathetic activity is believed to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the total production or excretion of NE and its metabolite DHPG, while providing a good measure of neurotransmitter turnover, does not assess exocytotic release of this neurotransmitter. Different studies have shown that the concentration of NE in venous plasma is a more sensitive indicator of ␣ 2 -adrenoceptor mediated regulation of NE release than DHPG [8][9][10][11][12]. Some studies have, however, suggested that plasma concentrations of DHPG may be used to monitor the effects of MAO inhibitors [13].…”
Section: Introductionmentioning
confidence: 94%